Knowledge Management: Alternatif Strategi Meningkatkan Kinerja Perusahaan - Siti Dyah Handayani (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
The more widespread application of knowledge management embodies the recognition of the importance of intangible assets in the form knowledge. Knowledge which is managed and developed will achieve competence and expertise, which ultimately could improve the competitiveness and performance. Several empirical studies support the opinion of experts, who had certainly found out that knowledge management could improve corporate innovation. Although it does not become the only factor, empirically, knowledge management could improve corporate performances. The implementation of knowledge management is not only suitable for commercial companies and large companies; knowledge management can also be applied to non-profit organizations (NPOs) and for small and medium enterprises (SMEs).